2014
DOI: 10.1002/jmv.24030
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and recombination of human parechovirus in children with acute gastroenteritis in Guangzhou, China

Abstract: Human parechovirus (HPeV), a member of Picornaviridae family, is a widespread pathogen causing a wide spectrum of diseases. Like other picornaviruses, HPeV genome recombination has been detected. A total of 322 fecal samples were collected from children outpatients in Guangzhou, China, including 42 (13.0%, 42/322) HPeV-positive samples detected in most of the infected children less than two years old. Seven HPeV genotypes (HPeV1, HPeV3, HPeV4, HPeV5, HPeV6, HPeV8 and HPeV14) were detected, among which, HPeV14,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…This is of significance as later studies have indicated that recombinants of HPeV3 may only emerge every 20 years or so, whereas recombinant strains of HPeV1, 2, 4, 5 and 6 appear to emerge roughly every 4 years192425262728. Some of those studies also looked at sequence variation in the structural region of HPeV1 and HPeV3 and estimated a substitution rate around 0.72% per year for HPeV1 and only 0.28–0.37% per year for HPeV31924.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is of significance as later studies have indicated that recombinants of HPeV3 may only emerge every 20 years or so, whereas recombinant strains of HPeV1, 2, 4, 5 and 6 appear to emerge roughly every 4 years192425262728. Some of those studies also looked at sequence variation in the structural region of HPeV1 and HPeV3 and estimated a substitution rate around 0.72% per year for HPeV1 and only 0.28–0.37% per year for HPeV31924.…”
Section: Discussionmentioning
confidence: 99%
“…Like other picornaviruses, recombination of HPeV often involves breakpoints at the very end of VP1 and thus may remove or add the RGD motif, or alternatively occur downstream in the non-structural coding region81920212223. Studies have indicated that recombinants of HPeV3 with other types may emerge less frequently and suggested that this may be due to a different cell tropism of HPeV3 compared to HPeV1, 2, 4, 5 and 6819242526272829.…”
mentioning
confidence: 99%
“…Like other picornaviruses, recombination in HPeVs has also been found, with breaking points at the capsid encoding and non-structural encoding regions [3134], among these recombination events most belonged to intra-genotype recombination. In the present study, a recombination event was detected in the non-structural region, which was inter-genotype recombination occurred between 3 HPeV strains belong three different genotypes and led to an HPeV-1 recombinant.…”
Section: Discussionmentioning
confidence: 99%
“…Intratypic recombination among HPeVs more frequently observed (1820) though intertypic recombination was also reported (4, 21). This study reported the first intertypic recombination occurring between HPeV5 and HPeV1 leading to an HPeV5 recombinant, which may highlight the evolutionary dynamics and diversity of HPeVs.…”
Section: Genome Announcementmentioning
confidence: 98%